Levels and health effects of maternal and infant exposure to chlorinated polyfluorinated ether sulfonic acid - Yujie CAO; Ying TIAN; Yu GAO (环境与职业医学)
Chlorinated polyfluoroalkyl ether sulfonic acid (Cl-PFESA, trade name F-53B), a substitute for perfluorooctane sulfonate (PFOS), notably featuring 6:2 Cl-PFESA and 8:2 Cl-PFESA as its primary components, are the most biologically persistent per-and polyfluoroalkyl substances (PFAS) currently known. Since its initial synthesis in China in 1975, F-53B has served as an antifogging agent in the electroplating industry for over four decades. Recently, F-53B has been detected across various matrix and human samples, ranking among the top three PFAS concentrations in maternal and umbilical cord blood sera in China, according to available epidemiological studies. Current limited epidemiological studies indicate that F-53B poses multiple adverse effects on maternal and infant health. Therefore, this article reviewed the exposure levels of F-53B in mothers and infants, along with its adverse health effects, thereby providing insights for evaluating the toxic effects of F-53B on maternal and infant health and establishing safety thresholds.